Performance Analysis Of Methods For Estimating Weibull Parameters For Wind Speed Distribution In The District Of Maroua - Kidmo Kaoga, D.; Danwe, R.; Doka Yamigno, S.; Djongyang, N. (University of Eloued جامعة الوادي, 2014)
In this study, five numerical Weibulldistribution methods, namely, the maximum likelihood method, the modified maximum likelihood method (MLM), the energy pattern factor method (EPF), the graphical method (GM), and the empirical method (EM) were explored using hourly synoptic data collected from 1985 to 2013 in the district of Maroua in Cameroon. The performance analysis revealed that the MLM was the most accurate model followed by the EPF and the GM. Furthermore, the comparison between the wind speed standard deviation predicted by the proposed models and the measured data showed that the MLM has a smaller relative error of -3.33% on average compared to -11.67% on average for the EPF and -8.86%on averagefor the GM. As a result, the MLM was precisely recommended to estimate the scale and shape parameters for an accurate and efficient wind energy potential evaluation.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 02
Keywords: empirical method; energy pattern factor method;graphical method;maximum likelihood method; modified maximum likelihood method;wind speed.